Evaluation of the Performance of Zakat and Infaq-Based Development Funds in Supporting the Community Economic Empowerment Program (International Journal of Economics Management and Social Science, 2026)
Community economic empowerment through the management of zakat and infaq funds has become a key strategy in efforts to improve welfare and reduce poverty in various regions. This study aims to evaluate the performance of zakat and infaq-based development funds in supporting community economic empowerment programs. A descriptive qualitative approach was used to deeply understand the processes, factors, and challenges faced in managing these funds. Data were collected through in-depth interviews, observations, and documentation studies from various stakeholders, including fund managers, beneficiaries, and relevant sources. The results indicate that the effectiveness of funds in increasing community economic empowerment is influenced by aspects of transparency, accountability, and community participation. This study recommends improving the fund management system, strengthening the capacity of managers, and developing programs oriented towards sustainability and long-term empowerment. These findings are expected to contribute to the development of more effective zakat and infaq fund management policies and practices for community economic empowerment.